Clinical effect of trimetazidine on prevention of contrast-induced nephropathy in patients with renal insufficiency: An updated systematic review and meta-analysis. Issue 9 (March 2017) - Ye, Ziliang; Lu, Haili; Su, Qiang; Guo, Wenqin; Dai, Weiran; Li, Hongqing; Yang, Huafeng; Li, Lang
Abstract: Background: With the continuous development of cardiac interventional medicine, the incidence of contrast-induced nephropathy (CIN) is increasing every year, which is a serious threat to people's physical and mental health. Trimetazidine (TMZ) is a type of anti-ischemic drug developed in recent years, which can significantly reduce the incidence of CIN. At present, a systematic review and meta-analysis was conducted to evaluate the clinical effect of TMZ on prevention of CIN in patients with renal insufficiency. However, the study did not include patients from other countries and speaking different languages. So we conducted this study to update the previous meta-analysis that investigated the effects of TMZ on prevention of CIN in patients with renal insufficiency, and provided some theoretical reference for clinical. Methods: By searching PubMed, Embase, the Cochrane Library, Web of Science, CBM, CNKI, VIP database, and Wang Fang database for randomized controlled trial, which is comparing TMZ versus conventional hydration for prevention of CIN. Two researchers independently screened literature, and then evaluated the quality of literature and extracted the relevant data. Stata 11.0 software was used for statistical analysis. Results: Finally, this updated review showed that 3 studies that were not included in the previous meta-analysis were included in our study (3 articles were published in the Chinese Journal, 1 study for CIN, 1 study for CIN, serum creatinine (Scr), and superoxide dismutase, 1 study for CIN and Scr), and 1 outcome (Scr) reflecting the change of renal function was additionally included in our study. Of the 932 studies, 6 randomized controlled trials met the criteria, including 377 patients in TMZ group and 387 patients in control group. This meta-analysis for all studies showed that TMZ can significantly reduce the incidence of CIN (relative risk 0.27, 95% confidence interval [CI] 0.16, 0.46, P  = 0.000), and can decrease the level of Scr after operation, including Scr of postoperative 24 hours (standardized mean difference [SMD] −0.30, 95% CI −0.51, −0.09, P  = 0.005), Scr of postoperative 48 hours (SMD −0.66, 95% CI −1.23, −0.10, P  = 0.022), and Scr of postoperative 7 days (SMD −0.74, 95% CI −1.36, −0.11, P  = 0.021). However, the Scr of postoperative 72 hours between TMZ group and control group has no statistical significance ( P  = 0.362). Conclusion: Our study showed that when comparing with conventional hydration, TMZ can significantly reduce the incidence of CIN and the level of postoperative Scr. Therefore, we could suggest that TMZ was superior to conventional hydration for the treatment of CIN in patients with renal insufficiency. However, due to the restriction of quality and number of included articles, it still needs to carry out multicenter, randomized, double-blind clinical trials to confirm this conclusion in the future.